THE MEDIATING ROLE OF SELF-EFFICACY ON THE EFFECT OF COPING STRATEGIES ON OCCUPATIONAL SATISFACTION (Third Sector Social Economic Review, 2020)
The aim of this study is to determine the components’ effects of the coping strategies of lawyers on occupational satisfaction and examine the mediating role of self-efficacy in this effect. In this study, which is designed as a quantitative research, the research population is composed of lawyers working in Hatay. Correlation and regression analysis were used to determine the relationships among variables by using data collected from 171 lawyers through the snowball sampling method with survey techniques. As a result of this study, it was found that there are positive and statistically significant relationships of problem solving and seeking support strategies on occupational satisfaction of lawyers. In accordance with another aim of this study, self-efficacy has a mediating effect on the relationship between two coping strategies (problem solving and seeking support) and occupational satisfaction. According to these results, it was stated that increasing the level of problem solving and seeking strategies of lawyers increased occupational satisfaction and also self-efficacy had a reinforcing effect on these relations. In addition to the theoretical and practical contribution of this research to the relevant literature, suggestions were also made to shed light on future studies.
Keywords: Coping Strategies; Self-Efficacy; Occupational Satisfaction; Mediating Effect